2017
DOI: 10.3389/fnagi.2017.00337
|View full text |Cite
|
Sign up to set email alerts
|

Cilostazol Suppresses Aβ-induced Neurotoxicity in SH-SY5Y Cells through Inhibition of Oxidative Stress and MAPK Signaling Pathway

Abstract: Alzheimer's disease (AD) is a slowly progressive form of dementia, characterized by memory impairment and cognitive dysfunction. AD is mainly characterized by the deposition of amyloid β (Aβ) plaques and intracellular neurofibrillary tangles in the brain, along with neuronal degeneration and high levels of oxidative stress. Cilostazol (CSZ) was recently found to suppress the progression of cognitive decline in patients with stable AD receiving acetylcholinesterase inhibitors. This present study aimed to clarif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
31
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 44 publications
4
31
1
Order By: Relevance
“…Based on the experimental results obtained in our study, inhibition of the MAPK signaling pathway was found to inhibit PCa cell proliferation, invasion and migration, as well as EMT. MAPKs are a family of serine-threonine kinases, which are activated by several factors and play central roles in the regulation of intracellular signaling essential for cell proliferation, differentiation, survival, development, death and transformation [32]. The MAPK signaling pathway has been widely investigated in various types of PCa therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the experimental results obtained in our study, inhibition of the MAPK signaling pathway was found to inhibit PCa cell proliferation, invasion and migration, as well as EMT. MAPKs are a family of serine-threonine kinases, which are activated by several factors and play central roles in the regulation of intracellular signaling essential for cell proliferation, differentiation, survival, development, death and transformation [32]. The MAPK signaling pathway has been widely investigated in various types of PCa therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The increase of glucose by vasodilation with cilostazol may protect synaptic loss and neuronal degeneration in AD patients. We found that cilostazol contributed to the increase of glucose in some specific regions in AD brain, and this increase is related to the cognitive improvement in this study [33][34][35]. Thus, the glucose uptake increase by cilostazol may prevent Aβ-induced impairment of glucose transport in neurons of mild AD and this glucose transport maintenance with cilostazol can delay cognitive deterioration.…”
Section: Discussionsupporting
confidence: 57%
“…It may be related to the neuroprotective effect of cilostazol. Animal studies also reported that cilostazol prevented memory impairment and protected brain oxidative stress [33,34], and also suppressed Aβ peptideinduced neurotoxicity and inhibited Aβ oligomerization [35]. Additionally, we suggested a hypothetical mechanism which can explain and understand dynamic relationships among Aβ, p-Tau, and glucose related to AD pathology and cilostazol effects on their dynamic interactions.…”
Section: Discussionsupporting
confidence: 52%
“…Aβ causes neuronal cell death in the development of AD, resulting in cognitive and behavioral deficits (28,29). The neuronal cell death is closely related to Aβ-induced oxidative stress and consequent activation of pro-apoptosis signaling, because antioxidative substances and inhibition of apoptosis signaling, alone or in combination, prevent the cell death (30)(31)(32). Astrocytes, a major glial cell type in the brain, participate in the neuropathogenic mechanisms after chronic exposure to Aβ (30).…”
Section: Discussionmentioning
confidence: 99%